COMPLEXITY OF PRACTICAL WORK IN PORTUGUESE PRIMARY SCIENCE TEXTBOOKS - Ferreira, Sílvia; Saraiva, Leonor (Investigações em Ensino de Ciências, 2021)
Practical work and textbooks have an important role in primary science education. This study analyses the complexity of practical work in Portuguese primary science textbooks. The level of complexity was appreciated by the level of conceptual demand of practical work, as given by the type of practical work, the complexity of scientific knowledge, the complexity of cognitive skills and the degree of relation between theory and practice. The explicitness of practical work was also analysed. The study followed an approach that combines quantitative and qualitative methods of analysis and a total of 176 units of analysis were evaluated from six science textbooks, chosen among the most selected in Portuguese primary schools. The results showed that textbooks evidence a tendency towards a low level of conceptual demand of practical work, considering the proposals for practical activities and the related evaluation questions. Practical activities, mainly focused on practical exercises and illustrative experiences, tend to mobilize scientific knowledge and cognitive skills of a low level of complexity and point out to an apparent relation between theory and practice. The evaluation questions present a lower level of conceptual demand. The results also showed a weak concern with the explicitness of the practical work. However, findings also indicated that there are differences between the textbooks.